2021
DOI: 10.33394/jollt.v9i3.3845
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison Between Sq5r and Fix–up Strategy in Reading Comprehension for Efl Secondary Level Learners

Abstract: This study investigates the Survey, Question, Read, Recite, Record, Reflect and Review (SQ5R) method and Fix–Up strategy to increase students’ reading comprehension of descriptive texts at Tenth grade of MAN 1 Takengon. The purpose of this research is to find out the comparison of strategies between Survey, Question, Read, Recite, Record, Reflect and Review and Fix–Up strategy. This study used quantitative research using experimental design. The sample of this study consisted of X-A and X-B classes. The X-A Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…The finding indicated that students could answer the questions correctly after applying those options. The finding was in line with Herwanis et al (2021) which claimed that this strategy could help students understand certain words and sentences.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The finding indicated that students could answer the questions correctly after applying those options. The finding was in line with Herwanis et al (2021) which claimed that this strategy could help students understand certain words and sentences.…”
Section: Discussionsupporting
confidence: 85%
“…More recently, a study conducted by Herwanis et al, (2021) sought to compare the fix-up options strategy to the Surveys, Questioning, Read, Recite, Record, Reflect, and Review (SQ5R) strategy for improving students' reading comprehension. They discovered that both strategies increased students' comprehension when using observation and tests for instruments.…”
Section: Previous Scientific Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the SQ4R method can be one good solution to the problems of selecting methods for teaching reading. This is in fact in line with some empirical evidence of the importance of the SQ4R method as one of the effective ways to enhance EFL learners ' reading comprehension (Alzu'bi, 2020;Ginting et al, 2021;Khusniyah, 2020;Mohamed Sayed Mohamed, 2020;Nurhidayat & Suwandi, 2021;Başar & Gürbüz, 2017;Khusniyah & Lustyantie, 2017;Herwanis et al, 2021;Simbolon et al, 2020;Rojabi, 2020). Qualitatively, EFL learners under study experienced EFL reading comprehension process by stepping into six phases, i.e., survey, question, read, recite, relate and review.…”
Section: Discussionsupporting
confidence: 84%
“…One of the effective strategies for reading is SQ4R. Numerous studies claimed that the SQ4R strategy can be used as an effective way to enhance EFL learners ' reading comprehension (Alzu'bi, 2020;Ginting et al, 2021;Khusniyah, 2020;Mohamed Sayed Mohamed, 2020;Nurhidayat & Suwandi, 2021;Başar & Gürbüz, 2017;Khusniyah & Lustyantie, 2017;Herwanis et al, 2021;Simbolon et al, 2020;Rojabi, 2020). In the SQ4R strategy, learners are not only required to increase reading comprehension by conventional ways in which learners are recognizing global ideas and detailed linguistic features in the text, but also enhance their critical competence where intellectual indigestion is optimized.…”
Section: Introductionmentioning
confidence: 99%